2021
DOI: 10.5811/westjem.2021.2.49675
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Contraceptive Services in the Emergency Department: A Cross-sectional Survey

Abstract: Introduction Unintended pregnancy disproportionately affects marginalized populations and has significant negative health and financial impacts on women, their families, and society. The emergency department (ED) is a promising alternative setting to increase access to sexual and reproductive health (SRH) services including contraception, especially among marginalized populations. The primary objective of this study was to determine the extent to which adult women of childbearing age who present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[16] In a survey of ED visitors seeking contraceptive management, the responders reported that their experience of ED-based contraception services was favorable. [15] The demand for ECPs at EDs has been increasing. [17] However, research on ED visits for ECP, including visits for sexual diseases or injuries, remains limited, [18,19] and ED-based research on the time interval between coitus and the ED visit is limited to a few surveys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] In a survey of ED visitors seeking contraceptive management, the responders reported that their experience of ED-based contraception services was favorable. [15] The demand for ECPs at EDs has been increasing. [17] However, research on ED visits for ECP, including visits for sexual diseases or injuries, remains limited, [18,19] and ED-based research on the time interval between coitus and the ED visit is limited to a few surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The ED has been designated as the primary center to provide ECPs. [5,14,15] Furthermore, the number of ED visits after sexual assault has increased greatly between 2006 and 2019. [16] In a survey of ED visitors seeking contraceptive management, the responders reported that their experience of ED-based contraception services was favorable.…”
Section: Introductionmentioning
confidence: 99%